(untitled) (Academicia Globe: Inderscience Research, 2025)
This article explores the significant role of digital technologies in enhancing the quality of education. It examines how digital tools, such as online platforms, multimedia resources, and virtual simulations, contribute to creating more interactive, flexible, and personalized learning environments. The article discusses the benefits of digital technologies, including improved student engagement, skill development, accessibility, and real-time data-driven insights. It also addresses the challenges that come with the integration of these technologies, such as the digital divide, teacher training, and technical infrastructure. Finally, it offers innovative solutions to ensure the effective use of digital technologies in education, emphasizing the importance of hybrid learning models, expanded access, and digital literacy.